How to track the need for digital disaster learning resources for prospective elementary school teachers? - Noviana, Eddy; Hadriana; Yustina; Erlinda, Sri; Kurniaman, Otang; Sari, Intan Kartika; Putri, Kuntum Sharfin; Raja Guk-guk, Elin Hotmaria (International Conference on Elementary Education, 2024)
In the current digital era, the need for digital learning resources in education is very important and urgent to develop. It includes developing digital disaster learning resources for prospective elementary school teachers. This article will discuss SWOT analysis (Strengths [S], Weaknesses [W], Opportunities [O], Threats [T]) as an instrument for conducting a needs analysis to develop digital disaster learning resources for prospective elementary school teachers. This research uses a literature study method, with research implementation stages consisting of (a) collecting reference sources, (b) verifying literature sources, and (c) conceptualization. From the research stages that have been carried out, the needs analysis instrument for developing digital disaster learning resources for prospective elementary school teachers can be classified into four forms, namely strength analysis (S) consisting of five question items, weakness analysis (W) consisting of three question items, opportunity analysis (O) consists of two question items, and threat analysis (T) consists of two question items. Based on this, it is necessary to carry out a SWOT analysis to prepare an analysis instrument for developing digital disaster learning resources for prospective elementary school teachers. The recommendation from the results of this study is that the needs analysis instrument using SWOT analysis can be adapted for use in needs analysis instruments for developing media and other learning resources.